Giardia Lamblia and Giardiasis (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Giardia lamblia is widespread enteric protozoan parasite of human and other mammals . Prevalence data suggest that 200 million people are infected with Giardia lamblia. The parasite has been discovered by van Leeuwenhoek in 1961. Life cycle of G.lamblia  has two stages trophozoite and cyst of which trophozoite is the pathogenic stage and cyst is infective stage and both of them found in fecal material of patient with giardiasis. The parasite transmitted mainly by oral –fecal route .Giardia infection which is characterized by malabsorbtion of small intestine and fatty diarrhea  . Pathogenicity of Giardia trophozoite occurs due to direct damage of intestinal lining or mechanical blockage of intestinal villi and absorption. Identification of parasite is based on recognized of trophozoite and cyst microscopically and also by detection of antigen from fecal sample .ELISA test ,Direct flurescentantibody test and PCR test are also helpful ,Giardia infection can be effectively treated by metronidazole as primary stapes of treatment.